The vintage years of eLearning in New Zealand schools - Nola Campbell (Flexible Learning Association of New Zealand, 2012)
This article reports on the early development in the 1980s and early 1990s of what is now known as eLearning in the New Zealand school sector. Consideration is given to the social, political, and educational influences that have informed this development, and the author describes some of the eLearning strategies that were adopted. An analysis of these trends and events provides the basis for some predictions of what the future might hold. The author has been involved in the development of eLearning in New Zealand throughout this period and combines personal insights with historical data.